De la gran transformación a la gran financiarización. Sobre Karl Polanyi y otros ensayos - Quiroz, Omar (Foro Internacional, 2019)
Keywords: From the Great Transformation to the Great Financialization (Book); book review

¿Cooptación o resistencia? Problematizando las estrategias legales y derechos de los movimientos sociales en el dominio socio-económico - Fierro, Alberto (Co-optation or resistance? Problematizing legal strategies and rights for social movements in the socio-economic domain., 2018)
This paper elaborates an analytical template to problematize the politics of legal strategies and rights. In the literature, scholars have been arguing that courts have an individualizing effect on collective struggles, or that (human) rights constitute neoliberal subjects. Yet, it is possible to open this theoretical understanding to further complexities: the inclusion of movements into certain governmentalities may have positive effects for their struggle. The discussion follows two main argumentative axes: first, social movements using legal tools and rights language are possibly deploying strategies of 'counter-conducts': exactly because the law is part and parcel of neoliberal governmentalities, it can constitute a strategic element to redirect and subvert established power relationships. Second, rights in the socio-economic domain (e.g. labor, housing and land) have specific properties which work against economic neoliberalism. Following a classic Polanyian argument, the idea of socioeconomic rights pulls away these goods from the market domain. This creates difficulties to the capitalist economic system, which is based on a rather strict conception of land and housing as commodities. (English)
Keywords: Derechos; contraconductas; counterconducts; estrategias legales; governmentality; gubernamentalidad; legal strategies; movimientos sociales; rights; social movements

Karl Polanyi. El Racionalismo Económico Como Motor De La Utopía Liberal - Goikoetxea Berdonces, Maialen (KARL POLANYI. THE ECONOMIC RATIONALISM AS THE MOTOR OF THE LIBERAL UTOPIA., 2018)
Karl Polanyi's main thesis is the effective separation of society and economy, placing the economy above the society. This artificial separation will be carried out by a series of theoretical tools and mechanisms -the introduction of fictitious goods and economic rationalism as a social premise- that will blind an overall view of the social panorama, focusing only on the economic aspects of it, causing that way, an unprecedented human crisis. (English)
Keywords: capitalism; capitalismo; economic rationalism; fictitious goods; liberal utopia; mercancías ficticias; racionalismo económico; utopía liberal

¿Incrustamiento sin espacio? Situando el comercio justo en la industria florícola ecuatoriana - Lyall, Angus (Embeddedness without a space? Situating fair trade in the Ecuadorian flower industry., 2015)
In the last two decades, Fairtrade International has consolidated as the largest fair trade certifier in the world. Much of its growth has involved the expansion of its practices from exclusively certifying cooperatives of smallholder farmers to regulating agroindustries and nonagricultural companies. In hired labor contexts, Fairtrade claims to improve labor and environmental conditions and promote local development and many researchers praise Fairtrade for "re-embedding" economic relations in social and ethnical ones. In this article, I highlight the testimonies of workers on three certified Ecuadorian flower plantations, who acknowledge many of these claims, but remind us that framing Fairtrade as a mechanism for "re-embedding" economic relations elides the desire among workers to leave the flower industry and re-embed their economic relations in local social space. Whereas Polanyi conceives of embeddedness in historically and geographically situated relations, I argue that academic approaches to Fairtrade often misappropriate his notion of the concept by employing it to describe abstract relations between consumers and workers. I place this concept in dialogue with the work of Henri Lefebvre on social space and territory to re-conceptualize what an embedded territorial development might look like under Fairtrade and to foreground the limits and contradictions of this mechanism. (English)
Keywords: Ecuador; LEFEBVRE, Henri; comercio justo; embeddedness; espacio social; fair trade; flower industry; incrustamiento; industria florícola; social economy; social space

Acerca del renovado interés por Karl Polanyi - Subirats, Joan (Sobre o interesse renovado de Karl Polanyi., 2014)
¿Cómo es posible que un libro escrito hace setenta años despierte hoy un renovado interés y que sirva para hacer mejores diagnósticos sobre la crisis económica y sus posibles alternativas? En este texto trataremos de dar respuesta a este interrogante, mostrando los elementos que hacen de la obra de Polanyi un buen punto de partida para observar la crisis de legitimidad política y los problemas de relación entre economía de mercado y sistema político. La crítica de Polanyi a la naturalización de la economía de mercado es hoy plenamente actual. (Spanish)
Keywords: bens comuns; bienes comunes; capitalismo; crises econômica; crisis económica; economia de mercado; economía de mercado; relaciones estado y sociedad; relações de estado e sociedade

El Debate Moderno Sobre Los Escritos Económicos Aristotélicos - Borisonik, Hernán (The modern debate on the Aristotelian economic writings., 2013)
The present article is a critical reading of the most important modern interpretations on Aristotle's economic writings. Firstly, the debate between the “primitivists" and the “modernists" (headed by Rodbertus, Bücher and Meyer) will be studied. Then, the readings of Karl Marx, Joseph Schumpeter, Karl Polanyi and Moses Finley, will be analyzed, considering these authors as the most renowned commentators of the Aristotelian economical legacy. (English)
Keywords: ARISTOTLE; Aristóteles; FINLEY, M. I. (Moses Israel), 1912-1986; MARX, Karl, 1818-1883; SCHUMPETER, Joseph Alois, 1883-1950; economic research; economics; economía; history of economics; primitivism and modernism; primitivismo y modernismo

Los aborígenes colombianos y las paradojas del desarrollo: el caso de los emberá katíos del Alto Sinú - Martínez Triviño, Ana Milena; Reyes Albarracín, Fredy Leonardo (Colombian indigenous and the paradoxes of development: the case of the emberá katios from High Sinú., 2013)
In 1992 the construction of the Urra I hydroelectric begins, one of the most ambitious energy projects in the recent history of Colombia. Located in the inhospitable jungle region of High Sinú -northwest of the Andean territory- the environmental license granted by government entities ignored the ecological and environmental impacts the work would entail, and also failed to recognize the presence of the emberákatio indigenous people, whose constitutional rights were violated. Following the arguments presented by the economist Karl Polanyi, the article explores the environmental, social and cultural consequences caused by the energy project, in addition to delving in the strategy of violence and extermination that paramilitarism created to disrupt the organizational processes for the emberákatios, which resulted in the disappearance and murder of indigenous leaders. (English)
Keywords: aborígenes; fictitiuos merchanidise; indigenous; mercado autorregulado; mercancías ficticias; paramilitarism; paramilitarismo; self-regulated market; violence; violencia

Contrastes entre las reformas laborales del Japón y la República de Corea - Yun, Ji-Whan (Revista Internacional del Trabajo, 2011)
El Japón y la República de Corea acometieron a finales de los años noventa una serie de reformas del mercado de trabajo que se han presentado muchas veces como meramente flexibilizadoras. Sin embargo, el autor sostiene —sobre la base del concepto de «doble movimiento» de Polanyi— que los dos conjugaron las medidas liberalizadoras con otras en pos de la estabilidad social. Tras estudiar las leyes adoptadas por uno y otro para reformar su mercado de trabajo y atenuar la dualidad del mismo, afirma que las diferencias se deben a que tienen procedimientos y entornos distintos para fijar sus líneas políticas.
Keywords: Corea; Japan; Japón; República de; comentario; flexibilidad del trabajo; política laboral; protección social; segmentación del mercado de trabajo; seguridad del empleo

Economía de mercado, globalización y migración: retos y rostros de las personas vulneradas globales. Un análisis desde Karl Polanyi - Franco, Jefferson Frenel Junior Pierrelus (Contextualizaciones Latinoamericanas, 2020)
Este ensayo pretende demostrar cómo el mercado autorregulado que pregonael neoliberalismo es una falacia y que tiende tarde que temprano a acabar odestruir las propias condiciones sociales, ambientales y culturales que aseguranla vida en el planeta. Basado en una globalización financierista, en la privatización yen la liberalización de mercado, ese modelo se ha convertido en la mayor fábrica deempobrecidos, logrando cooptar y subordinar a los Estados a sus designios a travésde las grandes empresas transnacionales e instituciones económicas internacionales.La neo-esclavitud, la miseria, la precariedad y la violencia se han instalado como unmodo de ser y de vivir, aunadas a la emigración, debido a esa explotación, extracciónde recursos naturales a ultranza que lleva a cabo ese modelo económico imperante.Hay voces, manifestaciones, como la de Karl Polanyi, que quieren poner un freno a esemolino satánico, llamado neoliberalismo.
Keywords: economía de mercado; globalización; globalization; market economy; migración; violence; violencia